Homo disruptus and the future church - Ungerer, André (HTS teologiese studies, 2019)
The Fourth Industrial Revolution is a phrase that is frequently heard in the media. This study explores the major changes that this revolution has installed for us. The Fourth Industrial Revolution is an umbrella term for many aspects, and the study takes note of the concepts like the Internet of Things, artificial intelligence, artificial general intelligence, artificial superintelligence, transhumanism and Homo digitalis. The spin-off effect of this revolution may cause possible disruptive effects on Homo sapiens by creating greater numbers of Homo disruptus. The term Homo disruptus is not a frequently used term, although it can be used in conjunction with the disruption that will be part of our future. Disruption may occur because of emerging technology, robotics, unemployment, digital dictatorships and exploitation, the side effects of Homo digitalis and transhumanism. The church will be part and parcel of this world, although the church does not have to be a victim and can play a significant role in anchoring Homo disruptus with the timeless message of the gospel and finding innovative ways to deal with their disruptive world.